Educational mobility of second-generation Turks : cross-national perspectives - Schnell, Philipp (IMISCOE research., 2014)
This definitive study investigates the variations in educational mobility of second-generation Turks in France, Austria and Sweden. The findings show that differences are most pronounced in the Austrian education system, can be seen clearly in France and are least pronounced in Sweden. Schnell underscores the importance of both individual characteristics and institutional ones, but the institutional arrangements of education systems are found to matter more for the outcome of this mobility process.